Keanekaragaman Spesies Kupu-Kupu (Lepidoptera) pada Habitat Eko-wisata Taman Bunga Merangin Garden Bangko Jambi - Bayu Kurniawan; Rila Rahma Apriani; Srianika Cahayu (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Butterflies play an important role in the balance of ecosystems and function as a bioindicator for clean/healthy environment. Degradation and fragmentation of natural habitats threat the population of butterflies. Habitat conservation through eco-tourism is an way to keep the existance butterfly species. This study aims to identify the  butterflies species, analyze species diversity, and abundance of butterflies (Lepidoptera) in the eco-tourism habitat of Merangin Garden Bangkang Jambi flower garden. Sampling was carried out five times at December 2018 to March 2019 using insect net. A total of 3 families from 16 species found. The species that dominated was Junonia orithya with 88 individuals (16.4%). The biodiversity value of butterflies species was 2.68. Diversity index is the lowest level of diversity. The types of flowers that bloom affect the high or low diversity index values. The most of butterflies found at 7.30 - 9.30 AM.